Pengaruh PAD dan DAU terhadap Kinerja Keuangan Pemda dengan Belanja Pegawai Sebagai Variabel Intervening: Studi Kasus pada Pemerintah Kabupaten dan Kota di Provinsi Bangka Belitung Tahun 2017-2021 - Risya Aulia; Imelda Sari (Juara: Jurnal Riset Akuntansi, 2023)
The purpose of this research is to examine the effect of regional own-source revenue and general allocation funds on local government financial performance with personnel expenditure as an intervening variable in district and city governments in Bangka Belitung province. The sample was determined using saturated sampling, with a total of 6 districts and 1 city so that the total observations of this study were 35 observations. The analytical method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and Sobel test. Testing the hypothesis used the t test with the Eviews Software test tool version 12. The conclusion in this research is partially, local revenue has a significant negative effect on personnel spending. While general allocation funds have no effect on personnel spending. Furthermore, partially local revenue has a significant negative effect on local government financial performance. Partially, general allocation funds have a significant negative effect on local government financial performance and partially personnel spending has a significant positive effect on local government financial performance. Regional original income has a significant negative effect on local government financial performance through personnel spending. General allocation funds have no effect on local government financial performance through personnel spending.